2011
DOI: 10.1097/mca.0b013e328341baee
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loading dose of atorvastatin before percutaneous coronary intervention on periprocedural myocardial injury

Abstract: Short-term pretreatment with a high dose of atorvastatin significantly reduces procedural myocardial injury in early PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 0 publications
1
39
1
Order By: Relevance
“…In addition, the NAPLES II trial showed that a single loading dose of atorvastatin (80 mg) within 24 h before PCI was effective in improving inhospital CV outcome (OR 0Á56 [CI 95% 0Á35-0Á89]; P = 0Á014), especially the recurrence of AMI (5% vs. 15%; P = 0Á04) in patients undergoing elective coronary angiography for symptomatic coronary artery disease [32]. More recently, several studies and a meta-analysis confirmed these findings, showing the effectiveness of a statin loading dose before PCI to improve short-term CV outcomes (RR 1Á08 [CI 95% 1Á02-1Á14]; P = 0Á01) [38,[40][41][42]. On the other hand, other clinical studies showed controversial results on this role for statins [28,30,34,36,37].…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undesupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, the NAPLES II trial showed that a single loading dose of atorvastatin (80 mg) within 24 h before PCI was effective in improving inhospital CV outcome (OR 0Á56 [CI 95% 0Á35-0Á89]; P = 0Á014), especially the recurrence of AMI (5% vs. 15%; P = 0Á04) in patients undergoing elective coronary angiography for symptomatic coronary artery disease [32]. More recently, several studies and a meta-analysis confirmed these findings, showing the effectiveness of a statin loading dose before PCI to improve short-term CV outcomes (RR 1Á08 [CI 95% 1Á02-1Á14]; P = 0Á01) [38,[40][41][42]. On the other hand, other clinical studies showed controversial results on this role for statins [28,30,34,36,37].…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undesupporting
confidence: 58%
“…However, vascular injury following coronary angioplasty and stent displacement is still frequent and strongly worsen short-and longterm event-free survival [26]. Several studies reported that preoperative administration of statins might reduce the incidence of adverse effects after PCI [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 3). The Atorvastatin for Reduction of MYocardial Damage During Angioplasty-Acute Coronary Syndromes (ARMYDA-ACS) [29] and Novel Approaches for Preventing or Limiting Events (NAPLES) II trials [32] are the first large clinical trials supporting the use of a loading dose of atorvastatin (80 mg) before coronary PCI, to improve the short-term outcomes.…”
Section: Statin-associated Benefits In Patients Admitted For Acs Undementioning
confidence: 99%
“…Yu and colleagues 18 reported the highest incidence of AST/ALT and CK elevations; however, these incidences were similar between statin and placebo groups. 26 The remainder of the studies either did not report or stated that no adverse effects attributable to statins were seen.…”
Section: Discussionmentioning
confidence: 98%
“…32 On the basis of the available evidence, all statin-naive patients (both ACS and stable angina) should be strongly recommended to receive statin-loading doses before PCI to reduce the incidence of PMI. [17][18][19][20][21][24][25][26] For patients on chronic statin therapy before PCI, strong consideration should be given to reload with statins, particularly if they present with ACS. 27 There is less evidence for patients on chronic statin therapy presenting with stable angina; however, because of the low risk associated with statin loading, it is reasonable to reload all patients on chronic statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Importantly, PCI itself causes an acute vascular and systemic inflammatory response, which is diminished by potent preprocedural antiplatelet (glycoprotein IIb/IIIa inhibitors, clopidogrel, and other P2Y12 inhibitors) and statin therapy. [9][10][11][12] Hence, periprocedural hsCRP monitoring could be of use in identifying high-risk patients and guiding adjunctive periprocedural therapy to improve PCI outcomes.…”
mentioning
confidence: 99%